2020
DOI: 10.1093/jac/dkaa250
|View full text |Cite
|
Sign up to set email alerts
|

Identification of compounds active against quiescent artemisinin-resistant Plasmodium falciparum parasites via the quiescent-stage survival assay (QSA)

Abstract: Background Quiescence is an unconventional mechanism of Plasmodium survival, mediating artemisinin resistance. This phenomenon increases the risk of clinical failures following artemisinin-based combination therapies (ACTs) by slowing parasite clearance and allowing the selection of parasites resistant to partner drugs. Objectives To thwart this multiresistance, the quiescent state of artemisinin-resistant parasites must be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(55 citation statements)
references
References 45 publications
(65 reference statements)
1
54
0
Order By: Relevance
“…However, despite ART-resistant genotype of F32-ART5, EC 50 values of ART were also similar for both strains (ranging from 11 to 19 nM, Mann–Whitney test p-value = 0.267) ( Table 4 ), due to the specific P. falciparum quiescence-based mechanism of ART-resistance leading to parasite cell cycle arrest during drug exposure. Therefore, evaluation of ( 3i ) with specific assays of artemisinin-resistance [ 33 , 34 , 35 ] was conducted and evidenced that this compound was active against the artemisinin-resistant parasites at the proliferative state but not at the quiescent state (see Supplementary Materials Figure S49 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, despite ART-resistant genotype of F32-ART5, EC 50 values of ART were also similar for both strains (ranging from 11 to 19 nM, Mann–Whitney test p-value = 0.267) ( Table 4 ), due to the specific P. falciparum quiescence-based mechanism of ART-resistance leading to parasite cell cycle arrest during drug exposure. Therefore, evaluation of ( 3i ) with specific assays of artemisinin-resistance [ 33 , 34 , 35 ] was conducted and evidenced that this compound was active against the artemisinin-resistant parasites at the proliferative state but not at the quiescent state (see Supplementary Materials Figure S49 ).…”
Section: Resultsmentioning
confidence: 99%
“…Chemosensitivity evaluation of ART-resistant parasites at the quiescent stage was performed on the strain F32-ART5 thanks to the quiescent-stage survival assay (QSA) [ 35 ]. D-sorbitol synchronized ring-stages parasites at 3% parasitemia (2% hematocrit) were first exposed to 700 nM of dihydroartemisinin (DHA) for 6 h to induce quiescence of artemisinin-resistant parasites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…10,13,14 Interestingly, the antimalarial drug atovaquone (ATQ, Table 1), which targets the bc1 complex of mitochondrial electron transport chain, 15 was reported to kill dihydroartemisinin-induced quiescent parasites. 16,17 Similarly, triclosan (TCS) and haloxyfop, which inhibit the FabI and acetyl-CoA carboxylase of the Plasmodium FAS-II pathway respectively, delayed the recrudescence of quiescent parasites after dihydroartemisinin treatment. 13 Simultaneously targeting the mitochondrion with ATQ and the apicoplast with TCS would thus be of valuable interest to face the issue of ART-resistance.…”
mentioning
confidence: 99%
“…Finally, the antimalarial drug mefloquine (MQ) was picked out as a relevant compound for drug combinations studies because it is one of the only two partner drugs used in ACTs to be reported as active on quiescent ART-resistant parasites. [17] We report here the evaluation of different combinations of two of these compounds, each targeting one essential pathway for quiescence survival: ATQ + TCS, ATQ + MQ, GW844520 + TCS. This evaluation was performed first on proliferating parasites then in an artemisinin resistance context on dihydroartemisinin (DHA)induced quiescent state, thanks to two specific tests, the recrudescence assay, 19 and the Quiescent-stage Survival Assay (QSA) for the best combination.…”
mentioning
confidence: 99%